Endoscopic features of low-grade dysplastic Barrett’s - He, Tony; Iyer, Kiran Gopinath; Lai, Mark; House, Eloise; Slavin, John L; Holt, Bronte; Tsoi, Edward H; Desmond, Paul; Taylor, Andrew C F (Endoscopy International Open, 2023)
Background and study aims Barrett’s esophagus (BE) with low-grade dysplasia (LGD) is considered usually endoscopically invisible and the endoscopic features are not well described. This study aimed to: 1) evaluate the frequency of visible BE-LGD; 2) compare rates of BE-LGD detection in the community versus a Barrett’s referral unit (BRU); and 3) evaluate the endoscopic features of BE-LGD.Patients and methods This was a retrospective analysis of a prospectively observed cohort of 497 patients referred to a BRU with dysplastic BE between 2008 and 2022. BE-LGD was defined as confirmation of LGD by expert gastrointestinal pathologist(s). Endoscopy reports, images and histology reports were reviewed to evaluate the frequency of endoscopically identifiable BE-LGD and their endoscopic features.Results A total of 135 patients (27.2%) had confirmed BE-LGD, of whom 15 (11.1%) had visible LGD identified in the community. After BRU assessment, visible LGD was detected in 68 patients (50.4%). Three phenotypes were observed: (A) Non-visible LGD; (B) Elevated (Paris 0-IIa) lesions; and (C) Flat (Paris 0-IIb) lesions with abnormal mucosal and/or vascular patterns with clear demarcation from regular flat BE. The majority (64.7%) of visible LGD was flat lesions with abnormal mucosal and vascular patterns. Endoscopic detection of BE-LGD increased over time (38.7% (2009–2012) vs. 54.3% (2018–2022)).Conclusions In this cohort, 50.4% of true BE-LGD was endoscopically visible, with increased recognition endoscopically over time and a higher rate of visible LGD detected at a BRU when compared with the community. BRU assessment of BE-LGD remains crucial; however, improving endoscopy surveillance quality in the community is equally important.
Keywords: Barrett's and adenocarcinoma; Endoscopy Upper GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE); Endoscopic resection (ESD, EMRc, ...); Quality and logistical aspects; Image and data processing, documentatiton